Necrophilia is Concealed But Not An Uncommon Sexual Deviation: Contributing Factors and The Way Forward Among Selected Mortuary Workers - Akinduyo, Tosin Emmanuel (International Journal of Research in Counseling and Education, 2024)
Across the world, evidence is emerging that sexual deviations are common across so many societies. The study investigated necrophilia as a concealed but not an uncommon sexual deviation; contributing factors and the way forward among selected mortuary workers. This qualitative study used interpretive phenomenological design. Data were collected from ten (10) mortuary workers who both worked at privately and government/publicly owned morgues in Kwara-State, Nigeria. Participants were judgmentally selected for the purpose of this study by revealing their lived experiences. A semi-structured interview was used as a data collection method. Data analysis was done through content analysis technique. This study showed mental stress, substance use, avoidance of responsibilities and ritualism were the chief contributory factors to necrophilia. Among other recommendations, constant programmes that will cater for the mental health of mortuary workers should be enforced.